2020
DOI: 10.1002/ppul.24665
|View full text |Cite
|
Sign up to set email alerts
|

Urine gastrin‐releasing peptide in the first week correlates with bronchopulmonary dysplasia and post‐prematurity respiratory disease

Abstract: Rationale Bronchopulmonary dysplasia (BPD) is associated with post‐prematurity respiratory disease (PRD) in survivors of extreme preterm birth. Identifying early biomarkers that correlate with later development of BPD and PRD may provide insights for intervention. In a preterm baboon model, elevated gastrin‐releasing peptide (GRP) is associated with BPD, and GRP inhibition mitigates BPD occurrence. Objective We performed a prospective cohort study to investigate whether urine GRP levels obtained in the first p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…An additional limitation is that our exclusion criteria did not include non-infectious diseases with a potential effect on the infant's metabolic state, such as BPD, severe IVH, and patent ductus arteriosus (PDA) [38,58,63,64]. The role of IVH and PDA in a VOC outcome has not yet been established and should be further investigated.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…An additional limitation is that our exclusion criteria did not include non-infectious diseases with a potential effect on the infant's metabolic state, such as BPD, severe IVH, and patent ductus arteriosus (PDA) [38,58,63,64]. The role of IVH and PDA in a VOC outcome has not yet been established and should be further investigated.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Although the pathogenesis of BPD remains unclear, the expression of various neuropeptides was found to be abnormal during the development of BPD [ 3 6 ]. Many studies based on traditional research methods have found that neuropeptides can be used as potential biomarkers for BPD [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Next, we describe some of the considerations and anecdotes we discovered in attempting to implement best practices for Team Data Science (Table 1). We believe addressing these practices was instrumental in the publication of 12 papers from these studies [4,17,[19][20][21][22][23][24][25][26][27]. It also enabled us to easily adopt subsets of the data for use in class projects in courses we have taught.…”
Section: Resultsmentioning
confidence: 99%